2016
DOI: 10.2147/opth.s102611
|View full text |Cite
|
Sign up to set email alerts
|

Time of maximum cycloplegia after instillation of cyclopentolate 1% in children with brown irises

Abstract: PurposeWe aimed to 1) determine the time of maximum cycloplegia after instillation of cyclopentolate 1% in children with brown irises, 2) evaluate the correlation between the pupillary reaction and time of maximum cycloplegia, and 3) identify any side effects of the medication.Patients and methodsThis was a prospective analytical study involving children aged 5 to 14 years who were attending refraction clinic. Cyclopentolate 1% was instilled three times at 10-minute intervals. The spherical equivalent, pupilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We performed cycloplegic refraction until the pupils are fully dilated in our study. However, there are some studies that found that the time of maximum cycloplegia was earlier than that of maximum mydriasis [ 18 , 29 ]. Thus, the time of the cycloplegic refraction performed may also vary from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…We performed cycloplegic refraction until the pupils are fully dilated in our study. However, there are some studies that found that the time of maximum cycloplegia was earlier than that of maximum mydriasis [ 18 , 29 ]. Thus, the time of the cycloplegic refraction performed may also vary from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Compared to atropine, effect of cyclopentolate starts and ends faster, and it has less side effects. [ 1 2 ] The cycloplegia effect of topically used 1% cyclopentolate is seen after 30–45 min after application and continues for up to 24 h.[ 3 4 ] Tropicamide also causes mydriasis and cycloplegia, since it is a muscarinic receptor antagonist like cyclopentolate. Although the cycloplegic effect of tropicamide is not as effective as cyclopentolate, it is used frequently for pupillary dilatation due to acting in a shorter time and having fewer side effects.…”
mentioning
confidence: 99%